Comparative Study of the Morphology of the Ovipositor of Platygaster diplosisae (Hymenoptera: Platygasteridae) and Aprostocetus procerae (Hymenoptera: Eulophidae) Two Parasitoids Associated with the African Rice Gall Midge, Orseolia oryzivora (Diptera: Cecidomyiidae) - Souleymane Nacro; Jean-Pierre Nénon (Psyche: A Journal of Entomology, 2009)
We studied the morphology of the ovipositor of Platygaster diplosisae (Hymenoptera: Platygasteridae) and Aprostocetus procerae (= Tetrastichus pachydiplosisae) (Hymenoptera: Eulophidae), two parasitoids associated with the African rice gall midge (AFRGM), and Orseolia oryzivora (Diptera: Cecidomyiidae). Scanning electron microscope techniques were used for this study. The ovipositor of P. diplosisae was short (40 μm), and most of the sensillae found on it were mechanoreceptors and located on the distal portion of the 3rd valvulae. These sensillae may be involved in selection of an egg or larval host. The shortness of this ovipositor may be an adaptation to a host whose egg envelope thickness is not more than 0.7 μm. The ovipositor of A. procerae was 30 times (1.2 mm) the length of the P. diplosisae ovipositor. It was not only well equipped with mechanoreceptive sensillae, but these sensillae were very diverse and distributed along the length of the valvulae. The 10 denticulations of the lancet of this ovipositor allow this parasitoid to exploit hosts that are not otherwise readily accesible. These two parasitoids share the same resource by infesting different life stages of the host. The ovipositor of each species of parasitoid enhanced resource sharing, due to its length and its sensillae type and distribution.